UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI PEWARISAN SIFAT MELALUI MODEL (STAD)SISWA KELAS 9C DI SMP NEGERI PAKUSARI JEMBER TAHUN PELAJARAN 2019/2020 - Sri Marhaening Utami; Soesy Sri Wulandari (Saintifika, 2020)
Abstract: Students of class 9C SMP Negeri Pakusari Jember have difficulty in understanding IPA, so the average value of daily repetition is still below 75, including in the Property Heritage material. The purpose of this research is the Model Student Team Achievement Division (STAD) can improve the learning outcomes of IPA Material Inheritance in 9C students of SMP Negeri Pakusari Jember in the academic year 2018/2019. The data obtained in this study are student learning outcomes at the end of each cycle, teachers' ability in managing learning is taken from observation sheets, student activities are taken from student observation sheets. For the results of observation in cycle I observation of 80% research activity, student activity 75% included in the good category, in cycle II observation of research activity 90% student activity 88% included in the excellent category. Similarly, with the average learning outcomes of evaluation cycle I of 65, for cycle II of 85, From the results of the evaluation it can be seen that there is a significant increase in the average learning outcomes of students from cycle I to cycle II is 1.05. Keywords: Inheritance, STAD Learning Model, IPA Learning Outcomes